Spectrophotmetric Determination of Cefadroxil in Bulk and Dosage Form Using Sodium Hydroxide - S. W. Shantier; E. A. Gadkariem; K. E. Ibrahim; H. A. El-Obeid (E-Journal of Chemistry)
A simple spectrophotometric method was developed for the determination of cefadroxil in pure bulk and in capsules forms. The method is based on a direct reaction between cefadroxil and sodium hydroxide (1 N). A product with λmax at 342 nm and molar absorptivity of 7.9x103 L mol-1 cm-1 is formed after heating cefadroxil with sodium hydroxide (1 N) for 30 minutes. The absorbance-concentration plot was rectilinear over the range 5-25 μg/mL with correlation coefficient values not less than 0.999. The detection limit (LOD) and quantification limit (LOQ) were 0.693 μg/mL and 2.31 μg/mL. The method was validated using the BP liquid chromatographic method for cefadroxil assay. The results obtained by the developed method for the capsules dosage form were statistically compared with those of the BP liquid chromatography method and evaluated at 95% confidence limits.